Optogenetic Dissection of Neural Circuits Underlying Stress-Induced Mood Disorders - Liu, Qing; Zhang, Zhinuo; Zhang, Wenjuan (Frontiers in Psychology, 2021)
Objectives: This review aims to i) summarize the literature on optogenetic applications of different stress-induced mood disorder models of the medial prefrontal cortex (mPFC) and its projection circuits, and ii) examine methodological variability across the literature and how such variations may influence the underlying circuits of stress-induced mood disorders. Methods: A variety of databases (PubMed, Web of Science, Elsevier, Springer, and Wiley) were systematically searched to identify optogenetic studies that applied to mood disorders in the context of stress. Results: Eleven studies on optogenetic stimulation of the mPFC and the effect of its efferent circuitry on anxiety- and depression-like behaviors in different rodent models were selected. The results showed that the optogenetics (i) can provide insights into the underlying circuits of mood disorders in the context of stress (ii) and also points out new therapeutic strategies for treating mood disorders. Conclusions: These findings indicate a clear role for the mPFC in social avoidance, and highlight the central role of stress reactivity circuitry that may be targeted for the treatment of stress-induced mood disorders.